Field trialling of a pulse airtightness tester in a range of UK homes - Cooper, Edward; Zheng, Xiaofeng; Wood, Christopher; Gillott, Mark C.; Tetlow, David; Riffat, Saffa; Simon, Lia De (Taylor & Francis, 2016)
A new low pressure ‘quasi-steady’ pulse technique for determining the airtightness of buildings has been developed further and compared with the standard blower-door technique for field-testing a range of typical UK homes. The reported low pressure air pulse unit (APU) has gone through several development stages related to optimizing the algorithm, pressure reference and system construction. The technique, which is compact, portable and easy to use, has been tested alongside the standard blower-door technique to measure the airtightness of a range of typical UK home types. Representative of the UK housing stock, the homes mostly have low levels of airtightness, resulting in poor energy performance, poor indoor air quality and poor thermal comfort. Some of these homes have been targeted for retrofitting and a quick, low cost and simple method for accurately determining their airtightness has clear advantages for correctly predicting the benefits of any improvements. A comparison between the results given by the two techniques is presented and the field trials indicate that the latest version of the pulse technique is reliable for determining building leakage at low pressure. Repeatability of multiple APU tests in the same house is found to be within +/-5% of the mean. A test where the leakage is increased by a known amount shows the APU is able to measure the change more accurately than the blower-door test. The APU also gives convenience in practical applications, due to being more compact and portable, plus it doesn’t need to penetrate the building envelope. The field trials demonstrate the pulse test has the potential to be a feasible alternative to the standard blower-door test.